INNOVATIVE WAYS OF THE SYSTEM IMPROVING OF GRADUATED PROFESSIONAL TRAINING OF OFFICERS OF THE SECURITY AND DEFENSE SECTOR OF UKRAINE THROUGH THE PRISM OF VIRTUAL AND AUGMENTED REALITY - Вікторія Аніщенко (Вісник Кафедри ЮНЕСКО «Неперервна професійна освіта ХХІ століття»)
Modern realities place new demands on the transformation of the paradigm of military education in general, especially on the professional training of officers of the security and defense sector of Ukraine, which should result in professional competence and a high level of readiness to perform complex situational, including combat, tasks in various types of professional activities. Approaches amendments to the acquisition of innovative knowledge, skills and abilities by officers of the security and defense sector of Ukraine are laid down in a number of domestic legal acts and the adoption of international experience in training officers using innovative technologies. The results of the study made it possible to identify a number of statements, namely: the result of the graduated professional training of officers of the security and defense sector of Ukraine should not only be the higher military education obtained by officers, but also the formation of professional competence, a high level of readiness to perform complex situational, including combat, tasks in various types of professional activities; to ensure the quality of the results (acquisition of innovative knowledge, skills and abilities by officers while studying in higher education institutions with specific learning conditions) is possible through the introduction of an innovative set of actions aimed at creating a new educational environment, revision of approaches to improving the didactic support of curricula and the choice of modern methods and teaching technologies; a special role in the realization of the research objective is played by understanding the use of innovative educational technologies, including virtual and augmented reality. Such technologies can significantly improve not only the learning outcomes, which can be determined by a number of criteria (innovativeness of the formed competencies, timeliness of their updating, importance for a particular type of professional activity, etc.), but also significantly deepen the personal understanding of the development of critical thinking, communication skills, leadership qualities, the level of responsibility for ensuring the safety of all personnel, making certain leadership decisions on actions in the context of preparation and conduct of combat operations, officers’ understanding of their personality, purpose, aspirations and values in their professional and daily life.